Kangaroo-mother care method: a documentary study of theses and dissertations of the brazilian nurse (2000-2017) - Luana Cláudia dos Passos Aires; Claudia Koch; Evangelia Kotzias Atherino dos Santos; Roberta Costa; Janifer Souza Mendes; Graciela Mendonça da Silva de Medeiros
ABSTRACT Objectives: to characterize theses and dissertations that address Kangaroo-Mother Care Method produced in Brazilian Graduate Nursing Programs from 2000 to 2017. Methods: a documentary study of qualitative approach. From a total of 207 papers, 185 were excluded and 22 were selected. Results: in 2006 and 2014 there was a higher number of master's dissertations. In 2001, 2013 and 2017, there were three productions of doctoral theses. Universidade Federal de Santa Catarina (Federal University of Santa Catarina) presented the largest number of publications, with five studies, followed by Universidade Federal da Bahia (Federal University of Bahia), with four. Final considerations: Kangaroo-Mother Care Method has been researched in Brazilian Graduate Nursing Programs, mainly from the qualitative approach, highlighting the importance, contributions and difficulties of its application as a public policy.